Insights On Entrepreneurship Education In Public Universities In Turkey: Creating Entrepreneurs Or Not? - (:unkn) unknown (ELSEVIER SCIENCE BV, 2011)
Entrepreneurship acts as a remedy for unemployment and growth problems that are caused by the recent global economic crisis are the major issues in the political agenda of all countries today. However, for improving entrepreneurship and creating entrepreneurs that can create new jobs, adequate human resources and knowledge base are strongly required on national level. Entrepreneurship education gains importance for building entrepreneurship driven economy by making individuals acquire entrepreneurial skills, knowledge and mindsets. As a significant part of the formal education on creating entrepreneurs, entrepreneurship courses in higher education need to be focused and priorly improved. In this context, this study aims to explore entrepreneurship education in public universities in Turkey. By this aim, we searched and analysed Web sites of 360 academic units including business administration and engineering faculties, science and technology, social sciences institutes of 95 public universities in Turkey. Research findings showed that entrepreneurship courses in public universities in Turkey are not sufficient to provide skills or mindsets that are required for creating entrepreneurs that can contribute to economic growth and employment for students. (C) 2011 Published by Elsevier Ltd. Selection and/or peer-review under responsibility 7th International Strategic Management Conference
Keywords: Entrepreneurship education; unemployment; higher education; courses; ECONOMIC-GROWTH